2019
DOI: 10.1111/rsp3.12238
|View full text |Cite
|
Sign up to set email alerts
|

Economic crisis, Cohesion Policy and the eroding image of the European Union at the regional level

Abstract: As a result of a combination of political and economic crises engulfing the European Union (EU)since 2008 has deteriorated considerably its image among the citizens, undermining its legitimacy and future. Cohesion Policy, providing funding for a variety of investment projects across the European territories that have a direct impact on the lives of the EU citizens, is one the key instruments at the disposal of the EU that could positively influence that image. But does it? The paper probes the extent to which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Smętkowski and Dąbrowski () analyse in depth the association between the implementation performance of Cohesion Policy and the support to the EU. While they confirm what found by Brasili et al (), namely, a non‐significant effect of absorption capacity of regions and citizens' positive perception of the EU, they draw a complex picture of the relationship between the extent of funding and EU support.…”
Section: Structure Of the Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Smętkowski and Dąbrowski () analyse in depth the association between the implementation performance of Cohesion Policy and the support to the EU. While they confirm what found by Brasili et al (), namely, a non‐significant effect of absorption capacity of regions and citizens' positive perception of the EU, they draw a complex picture of the relationship between the extent of funding and EU support.…”
Section: Structure Of the Special Issuementioning
confidence: 99%
“…Cohesion Policy could be a powerful tool for promoting European identity, if the target of reduction of inequality within the EU is achieved (Aiello et al, ; Capello & Perucca, ; Dąbrowski et al, ). At the same time, however, this is likely to happen only if effective strategies of information, communication and involvement will be developed and implemented (Brasili et al, ; López‐Bazo & Royuela, ; Smętkowski & Dąbrowski, ).…”
Section: Structure Of the Special Issuementioning
confidence: 99%
“…Recently, this issue received great attention, witnessed by the funding of two Horizon 2020 projects 6 (Capello and Perucca, 2018;Aiello et al, 2019), aimed at understanding the relationship between Cohesion Policy implementation and citizens' identification with Europe. This stream of research generally pointed out a positive association between EU funding and European identity, subject however to the mediation of several factors, namely the level of awareness and satisfaction with the actions undertaken (Capello and Perucca, 2019), the implementation of effective strategies of information, communication and the involvement of the local population (López-Bazo & Royuela, 2019;Smętkowski & Dąbrowski, 2019). Coherently with this evidence, in the context of this paper Cohesion Policy is expected to decrease the identity gap in favour of national over European identity.…”
Section: The Determinants Of the Identity Imbalancementioning
confidence: 59%
“…Last but not least, we confirmed that the scale of funding also matters. Even though previous research suggested that the relationship between magnitude of funding and support for the EU is not straightforward (see Aiello, Reverberi, and Brasili 2019;Capello and Perucca 2019;Dąbrowski, Stead, and Mashhoodi 2019;Smętkowski and Dąbrowski 2019), the evidence from from stakeholder interviews and focus groups conducted, does suggest that the relatively small allocation of funding to the Dutch regions is hardly noticeable and can only have a limited impact on for positive EU identification. One of its anticipated effects of Cohesion Policy is to foster greater citizen attachment to the EU.…”
Section: Discussionmentioning
confidence: 92%